Long Non-Coding RNA Small Nucleolar RNA Host Gene 5 (SNHG5) Regulates Renal Tubular Damage in Diabetic Nephropathy via Targeting MiR-26a-5p - Cai, Qing; Wang, Chao; Huang, Li; Wu, Chen; Yan, BingChao; Chen, Ting; Li, Qinjun; Wang, Ling (Hormone and Metabolic Research, 2021)
The study explored the diagnostic value of SNHG5 in diabetic nephropathy (DN) and investigated the role and mechanism on DN via establishing the in vitro HK2 cell model. This study recruited 62 types 2 diabetes mellitus (T2DM) patients, 58 DN patients and 60 healthy controls (HC). The expressions of serum SNHG5 and miR-26a-5p were measured by RT-qPCR analysis. The diagnostic value of SNHG5 in DN was assessed by ROC curve. The in vitro cell model was built to estimate the effects of SNHG5 on cell viability, cell apoptosis, inflammation response and oxidative stress. Serum SNHG5 was increased in DN patients (relative expression: 2.04±0.34) and had the diagnostic value in DN. After HK2 cells were treated with high glucose, the cell viability decreased and apoptosis increased, and the production of inflammatory cytokines and ROS enhanced significantly. It was noticed that inhibition of SNHG5 could reverse the above phenomenon caused by high glucose. Besides, serum miR-26a-5p was diminished in DN patients, and luciferase reporter gene revealed that miR-26a-5p is direct target of SNHG5. These results indicated that inhibition of SNHG5 may mitigate HG-induced renal tubular damage via targeting miR-26a-5p, which providing a new insight into the mechanism of renal tubule damage in DN patients.
Keywords: SNHG5; miR-26a-5p; diabetic nephropathy; diagnosis